Рішення задачі обмеження просторів невизначеності - Diduk, N. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
It is shown that the notion of the simple subspace of an uncertainty space, which is constructed using the formal methods of Bourbaki’s theory of mathematical structures, cannot be a restriction problem solution because it does not meet the demand for succession in the development of the uncertainty mathematical apparatus. To construct the subspaces that meet the demand, the even versions apparatus is applied to simple subspaces. Examples of even subspaces are considered.